The issues of the basic principles of the criminal process - Łaskawski, Grzegorz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
The design of the criminal process is based on general assumptions adopted by the legislator as optimal due to the value system in force at a given place and time. Considerations covering issues related to the model of criminal proceedings are mainly determined by procedural rules, which to a greater or lesser extent result from criminal procedural norms. It can be said that they are a kind of concepts shaping the process, indicating its individual features, through which its characteristic elements are manifested.

Ukształtowanie procesu karnego opiera się na ogólnych założeniach przyjętych przez ustawodawcę jako optymalnych ze względu na obowiązujący w danym miejscu i czasie system wartości. Rozważania obejmujące zagadnienia związane z modelem postępowania karnego w głównej mierze determinowane są przez zasady procesowe, które w większym lub mniejszym stopniu wynikają z norm karnoprocesowych. Można powiedzieć, że są one pewnego rodzaju kształtującymi proces koncepcjami wskazującymi na jego indywidualne cechy, przez które przejawiają się charakterystyczne dla niego elementy.
Problematyka naczelnych zasad procesu karnego
Keywords: criminal procedure; principles of the criminal procedure; model of the criminal procedure; procedura karna; zasady procesu karnego; model procesu karnego